Thresholds for PSA doubling time in men with non‐metastatic castration‐resistant prostate cancer. (30th April 2017) - Howard, Lauren E.; Moreira, Daniel M.; De Hoedt, Amanda; Aronson, William J.; Kane, Christopher J.; Amling, Christopher L.; Cooperberg, Matthew R.; Terris, Martha K.; Freedland, Stephen J.
Abstract : Objectives: To examine whether prostate‐specific antigen doubling time (PSADT) correlates with metastases, all‐cause mortality (ACM), and prostate cancer‐specific mortality (PCSM) and to identify PSADT thresholds that can be used clinically for risk stratification in men with M0 castration‐resistant prostate cancer (CRPC). Materials and Methods: We collected data on 441 men with M0 CRPC in 2000–2015 at five Veterans Affairs hospitals. Cox models were used to test the association between log‐transformed PSADT and the development of metastasis, ACM and PCSM. To identify thresholds, we categorized PSADT into 3‐month groups and then combined groups with similar hazard ratios (HRs). Results: The median (interquartile range) follow‐up was 28.3 (14.7–49.1) months. As a continuous variable, PSADT was associated with metastases, ACM and PCSM (HR 1.40–1.68, all P < 0.001). We identified the following PSADT thresholds: <3 months; 3–8.9 months; 9–14. months; and ≥15 months. As a categorical variable, PSADT was associated with metastases, ACM and PCSM (all P < 0.001). Specifically, PSADT <3 months was associated with an approximately ninefold increased risk of metastases (HR 8.63, 95% CI 5.07–14.7) and PCSM (HR 9.29, 95% CI 5.38–16.0), and a 4.7‐fold increased risk of ACM (HR 4.71, 95% CI 2.98–7.43) on multivariable analysis compared with PSADT ≥15 months. The median times to metastasis for patients with PSADT <3, 3–8.9, 9–14.9 and ≥15 months were 9, 19, 40 and 50 months, respectively. Conclusion: Prostate‐specific antigen doubling time was a strong predictor of metastases, ACM and PCSM in patients with M0 CRPC. As with patients at earlier disease stages, <3, 3–8.9, 9–14.9 and ≥15 months are reasonable PSADT thresholds for risk stratification in men with M0 CRPC. These thresholds can be used for selecting high‐risk men for clinical trials.